2020
DOI: 10.1111/imcb.12310
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L2+ wound zone macrophage‐like cells display M1/M2‐mixed activation and restrain the effector Th1 responses

Abstract: Depending on the microenvironment conditions, macrophages display phenotypic and functional heterogeneity. This study characterized the programmed cell death-ligand 2 (PD-L2)-expressing macrophage-like cells drained from surgical wound zones, and investigated their influence on helper T (Th) cell responses. Although all CD14 + myeloid cells possessed macrophagelike features, CD206 + and CD163 + cells constituted a specific subpopulation with high PD-L2 expression. There was a modest correlation between the PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…When macrophages are stimulated with IL4 (with or without IL13, which also signals through the IL4Rα; hereafter we used a combination of IL4+IL13 to harmonize the results with previous studies [ Kratochvill et al, 2015b ]), a characteristic gene expression program is activated, which was first described as “alternative activation” ( Gordon & Martinez, 2010 ) and often referred to as “M2.” The physiology of only a handful of M2-associated targets, such as Arg1 and PD-L2, are understood in terms of their relationship to M2 functions in type 2 immunity and metabolic maintenance of OXPHOS, which is essential for the M2 phenotype ( Pesce et al, 2009 ; Huber et al, 2010 ; Gundra et al, 2017 ; Van de Velde et al, 2017 ; Baardman et al, 2018 ; Wang et al, 2018 ; Tavukcuoglu et al, 2020 ). To begin to dissect the influence of TNF on M2 gene expression in molecular terms, we chose one M2 target, Retnla (encoding RELMα), as a paradigmatic gene induced by IL4+IL13 and negatively regulated by TNF ( Kratochvill et al, 2015b ).…”
Section: Resultsmentioning
confidence: 99%
“…When macrophages are stimulated with IL4 (with or without IL13, which also signals through the IL4Rα; hereafter we used a combination of IL4+IL13 to harmonize the results with previous studies [ Kratochvill et al, 2015b ]), a characteristic gene expression program is activated, which was first described as “alternative activation” ( Gordon & Martinez, 2010 ) and often referred to as “M2.” The physiology of only a handful of M2-associated targets, such as Arg1 and PD-L2, are understood in terms of their relationship to M2 functions in type 2 immunity and metabolic maintenance of OXPHOS, which is essential for the M2 phenotype ( Pesce et al, 2009 ; Huber et al, 2010 ; Gundra et al, 2017 ; Van de Velde et al, 2017 ; Baardman et al, 2018 ; Wang et al, 2018 ; Tavukcuoglu et al, 2020 ). To begin to dissect the influence of TNF on M2 gene expression in molecular terms, we chose one M2 target, Retnla (encoding RELMα), as a paradigmatic gene induced by IL4+IL13 and negatively regulated by TNF ( Kratochvill et al, 2015b ).…”
Section: Resultsmentioning
confidence: 99%
“…(2) TAMs secret the immunosuppression cytokines regulate the T cell-induced ant-tumor immunity, including IL-10, IL-6, PGE2, and TGF-beta1 [ 97 ]. (3) TAMs express PD-L1 and PD-L2 and participate exhaustion of CD8 + T cell by cell–cell interaction[ 98 , 99 ].…”
Section: Tumor-associated Macrophagementioning
confidence: 99%
“…Interestingly, IRF1 is the key factor of PD-L1 promoter function, while PD-L2 is mainly regulated by STAT1/3 [ 33 ], which also explain our results that only PD-L2 is upregulated in LXN −/− macrophages. It has been reported that PD-1 ligands (PD-Ls) contribute to the M2 polarization and immunosuppressive effects of macrophages [ 48 ], and PD-L2 expression correlated with other established markers for alternatively activated macrophages [ 49 ]. As early as ten years ago, Huber et al reported that PD-L2 appears to be a more specific and distinctive marker for M2, and IL-4 induced the expression of PD-L2 on classically activated macrophages, however, LPS increased the expression of PD-L1 on M2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%